A Multi-Session Attribution Modification Program for Children with Aggressive Behaviour: Changes in Attributions, Emotional Reaction Estimates, and Self-Reported Aggression. Issue 5 (September 2015) - Vassilopoulos, Stephanos P.; Brouzos, Andreas; Andreou, Eleni
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Research suggests that aggressive children are prone to over-attribute hostile intentions to peers. Aims: The current study investigated whether this attributional style can be altered using a Cognitive Bias Modification of Interpretations (CBM-I) procedure. Method: A sample of 10–12-year-olds selected for displaying aggressive behaviours was trained over three sessions to endorse benign rather than hostile attributions in response to ambiguous social scenarios. Results: Compared to a test-retest control group (n = 18), children receiving CBM-I (n = 16) were less likely to endorse hostile attributions and more likely to endorse benign attributions in response to a new set of ambiguous social situations. Furthermore, aggressive behaviour scores reduced more in the trained group than in the untrained controls. Children who received attribution training also reported less perceived anger and showed a trend to report more self-control than those in the control group. Conclusions: Implications of these findings are discussed.